The planning process for work with children psychological aspects - Stonys, B. (Psichologija, 1968)
The author’s objecting, using 4th grade students’ classroom observation, interviews, and analysis of papers, was to establish some specific psychological features of working with primary school children in the lesson planning process. The students in experimental classes had to make an enclosed stroller from stencils, using the same model of stroller. After a short briefing the students had to individually, before starting to work, describe what plan they intend to follow. The data obtained showed that the decision to begin the task of analysis, as a rule, had to be performed "inside" and hastily. It was found that a hastily performed analysis had a negative effect on task itself. In an effort to begin work as soon as possible, students comprehended the model superficially, giving it insufficient attention. Initially, it appeared that many children know how to work. However, after getting started, they quickly realized that they cannot successfully complete the task. This shows that the students did not have differentiated individual component parts for a consistent perception of what was going on during this experiment. It was established that the typical haste manifests itself attempt to see the results of their work as soon as possible. Therefore, the student works in a hurry, without distinguishing significance for some operations and disregarding the requirements of working accurately and consistently. Often in such cases the results are not satisfactory. Failure to plan their actions and consciously apply them to the objective hinders their ability to deal with complex tasks in the future. Analysis of student written work plans shows that they, as a rule, only enumerate individual operations (and not always correctly). The whole of the action plans is usually expressed in two logical relationships: conjunction and disjunction. Not a single written work contained a justification for working actions. These facts show that students of a given experiment often distinguish minor attributes and in the early stages have yet to clearly imagine the final result of their activities. The author provides specific pedagogical guidelines on the basis of the research material as to how to improve working methods of conducting lessons.